The Effect of Foliar Spraying with Calcium Chloride and Fertilization with Fish Protein Hydrolysate on the Growth and Yield of Some Cucumber Hybrids Grown in Plastic Houses - Aqila Jumaah Hachim; Jamal Abdul Redha AL-Rabea'a; Asmahan Shayal Abdalkarim; fatimah mahdi jasem (University of Thi-Qar Journal of agricultural research, 2025)
The study was conducted to investigate the effect of foliar spraying of calcium chloride and fish protein hydrolysate at thestage of 4-5 true leaves on the growth and yield of some cucumber hybrids Sayff, Shady, Darina, Super Faris and Ballistic.The study included eight factorial treatments that are possible combinations between four levels of calcium chloride (3, 2,1, 0%) for the hybrids sayff and shady and the addition of fish protein hydrolysate (0, 2, 4, 6)% for the hybrids Darina,Super faris and Ballistic. The results showed that the hybrid Shady was significantly superior with an increase of 11.36% inplant height, 6.31% in stem diameter, 24.39% in fresh weight of the plant, 13.48% in dry weight of the plant, 4.29% inmoisture percentage, 15.24% in average weight of the fruit, 18.16% in vitamin C content of the fruit, and 9.99% in thepercentage of potassium ions penetrating the fruit. 38.97% in the calcium content of fruits compared to the Sayff variety.While the plants of the Sayff variety were superior significantly and by an increase of 12.92% in the early productivity ofthe plastic house compared to the plants of the Shadi variety. The plants are sprayed with calcium chloride.and treated witha concentration of 3% were superior significantly in the fresh weight of the plant by an increase of 14.73% in the calciumchloride content of the fruits by 292.83% and a significant decrease in the percentage of potassium ions penetrating thefruits and a significant increase in the total productivity of the house by 19.98% compared to the comparison treatment.Plants treated with 6% fish protein hydrolysate were significantly superior in all of the rated vegetative traits, root andflower growth indicators and total yield. The Darina variety also outperformed the rest of the varieties in fruiting traits andtotal yield.